Who depends on why: Toward an endogenous, purpose‐driven mechanism in organizations' reference selection - Luger, Johannes (Strategic Management Journal, 2023)
Research Summary This paper investigates how firms select reference organizations, that is, other firms to which they compare themselves. We question the exogenous nature of references (i.e., them being defined via industry‐categorizations) but suggest that, via motivations or purposes, firms endogenously select them. We evaluate our findings when analyzing proprietary data on hotels' self‐selection of comparison‐hotels. In support of our arguments, we find that in situations of increased uncertainty regarding firms' own relative abilities and standing, firms make adjustments to their selected references toward more similar ones. This enables them to obtain more diagnostic information about their relative abilities and this effect holds constant of (exogenous) industry‐entry or exit events. Our findings contribute to an updated understanding about the role of comparison organizations in firms' decision‐making. Managerial Summary Prior work shows that comparisons with other firms (i.e., references) play an important role for our understanding of firms' decision‐making. For example, performance comparisons with references can trigger search or a decision‐need, ultimately, leading to acquisition‐decisions, new‐product‐introductions, and the like. When questioning the selection of such references, prior work has typically derived them from (exogenous) industry‐categorizations. We review this practice by relying on rare, longitudinal data on firms' reference self‐selection. When controlling for industry level effects, we find that firms adapt references as a function of changes in their comparison needs (e.g., self‐assessment). This is important because it implies an endogenous reference selection mechanism and shifts the attention from industry‐categorizations toward an understanding of comparison needs and their emergence when attempting to understand firms' decision‐making.